2002
DOI: 10.1007/s004150200063
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of the localized girdle sensation of mid-trunk (false localizing sign) appeared in cervical compressive myelopathy patients

Abstract: Cervical compressive myelopathy patients sometimes show localized girdle sensation in the mid trunk (so-called false localizing sign). This symptom often confuses physicians, but the clinical features and mechanism of this symptom are still unclear. We investigated the clinical features and possible mechanism. In each of five cases of cervical compressive myelopathy disease with and without mid-truncal girdle sensation, the clinical features, degree and shape of cord compression were analysed. The girdle sensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…[3] Findings are similar in cases published by Adams KK et al [4] were he showed case series of 4 peoples with cervical myelopathy with false localizing sign. Findings also found to be similiar with the cases published by Ochiai H et al [5] Ochiai H et al compared cervical compressive myelopathy patients with and without girdle like sensation (false localizing sign) to evaluate for the reason of sensation, he could not find any correlation between sensation and level of cord compression. Another study by Adams KK et al showed 4 men with mostly lower limb weakness with girdle like sensation with Thoracic MRI normal which showed myelopathy in cervical MRI concluded that the diagnosis may be delayed because of false localizing sign (girdle sensation).…”
Section: Discussionsupporting
confidence: 72%
“…[3] Findings are similar in cases published by Adams KK et al [4] were he showed case series of 4 peoples with cervical myelopathy with false localizing sign. Findings also found to be similiar with the cases published by Ochiai H et al [5] Ochiai H et al compared cervical compressive myelopathy patients with and without girdle like sensation (false localizing sign) to evaluate for the reason of sensation, he could not find any correlation between sensation and level of cord compression. Another study by Adams KK et al showed 4 men with mostly lower limb weakness with girdle like sensation with Thoracic MRI normal which showed myelopathy in cervical MRI concluded that the diagnosis may be delayed because of false localizing sign (girdle sensation).…”
Section: Discussionsupporting
confidence: 72%
“…However, more distant sensory and motor signs may be observed with cord pathology, whose explanation is altogether more challenging. Compressive cervical myelopathy may produce a false localising thoracic sensory level, 29 sometimes called a mid thoracic girdle sensation, 30 in addition to lower limb weakness and hyperreflexia. Similarly, lumbar spinal disease may be simulated by more rostral pathology; for example, urinary retention, leg weakness, and lumbar sensory findings may be the presenting features of high thoracic cord compression, with clinicoradiological discrepancy of as much as 11 segments.…”
Section: Foramen Magnum and Upper Cervical Cord Lesionsmentioning
confidence: 99%
“…This observation led them to suggest that ischaemia in the watershed zone of the anterior spinal artery, affecting the medial portion of the laminations of the spinothalamic tract, was the causative mechanism for the girdle sensation, rather than direct compression of spinothalamic fibres. 30 Jamieson et al, however, favoured venous obstruction with ensuing intramedullary stasis and hypoxia as the explanation for remote phenomena. 31 Of course, different cases may have different pathogenesis, and/or more than one mechanism may be operating in any one case.…”
Section: Foramen Magnum and Upper Cervical Cord Lesionsmentioning
confidence: 99%
“…In monkeys, Taylor and Byrnes [7] found that spinal cord compression at the C2–3 level led to congestion of the spinal venous plexus, degeneration of the ventral horn cell, and posterior horn hemorrhage at the C8–Th1 level. Ochiai et al [5] also suggested a relationship between FLSs and ischemia in the anterior spinal artery due to decreased superficial perception, but normal deep sensation in patients of severe compression from the ventral side of the spinal cord. They also reported that compression from the ventral side was significantly stronger in the FLSs group (upper-limb type) than in the non-FLSs group (whole-body type).…”
Section: Discussionmentioning
confidence: 99%
“…However, few long-tract symptoms are pathognomonic of specific perceptual disorders in the upper cervical cord, and no symptoms have been identified as being specific to the C1–2 level segment. Furthermore, although FLSs have been described in lower cervical cord lesions, few reports have examined FLSs at the upper cervical cord level, particularly at the C1–2 level [2345]. In this report, we describe the clinical features of cervical myelopathy at the C1–2 level.…”
Section: Introductionmentioning
confidence: 93%